Women and power : education, religion and identity - Mejiuni, Olutoyin (Dakar, Senegal : Council for the Development of Social Science Research in Africa (CODESRIA), 2013)
Education is an important tool for the development of human potential. Organizations and individuals interested in development consider knowledge, skills and attitudes, obtained through formal, non-formal and incidental learning, as invaluable assets. Therefore, it is necessary to reflect on fundamental elements that shape the process through which education is attained: How do people learn, and what are the conditions that facilitate effective learning? Answers to these questions demonstrate that no education can be politically neutral, because there is no value-free education. The traditiona.
1. The Methodology; 2. Women's Civic-Political Participation Towards an Equitable and Humane Democratic Order; 3. The Subordinate Role of Women in the Private and Public Spheres; 4. Who am I? Prescribing Women's Identities; 5. The Violence of Power: Power Relations and Women's Experience of Violence; 6. Women's Identities and Power; 7. Is Formal Education Empowering?; Conclusion and Recommendations.
Includes bibliographical references (pages 189-194).
Print version record.
Master record variable field(s) change: 050
Keywords: Women -- Nigeria -- Social conditions; Feminism and education -- Nigeria; Education -- Political aspects -- Nigeria; Women and religion -- Nigeria; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Popular Culture; Education -- Political aspects; Feminism and education; Women and religion; Women -- Social conditions; Nigeria; Electronic books